From Culture to Science: Exploring Scientific Knowledge in the Making of Wadi, a Traditional Dish of the Dayak and Banjar - Silvita; Opik Prasetyo; Ulya Ruwaida; Zevira Fransisca Aurora; Rina Oktaviana (Postgraduate, University of Mataram, 2025)
Traditional food processing practices often contain implicit scientific knowledge that can be systematically analyzed and explained using modern science. This study examines the scientific knowledge embedded in the traditional preparation of Wadi, a fermented fish product of the Dayak and Banjar communities. The research aims to identify and describe forms of scientific knowledge represented in each stage of the Wadi-making process. This study employed a qualitative descriptive method using documentation analysis. Data were collected from selected written and visual sources that clearly describe the stages of Wadi production. The data were analyzed by mapping traditional practices to scientific concepts in food science. The results indicate that the preparation of Wadi embodies multiple forms of scientific knowledge, including osmosis in the salting process, salt-based preservation through microbial inhibition, lactic acid fermentation, moisture control, and biochemical transformations such as protein hydrolysis. These findings demonstrate that traditional culinary practices are not merely cultural activities but also reflect systematic scientific knowledge consistent with principles of microbiology, biochemistry, and food preservation. In conclusion, the scientific knowledge identified in the making of Wadi has strong potential to support contextual and culturally relevant science learning by connecting everyday practices with formal scientific concepts.